ANALISIS PENGEMBANGAN KAPASITAS ORGANISASI KANTOR SATUAN POLISI PAMONG PRAJA KABUPATEN LAHAT - Yuswijaya Yuswijaya (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
The variable in this research is the organization capacity buiilding of Lahat District Administrative Police (Pamong Praja Police) Unit Office. The research deploys a quantitative approach and a descriptive analisys method. The research aims at exploring possible approaches to developing the organization capacity of Lahat District Administrative Police (Pamong Praja Police) Unit Office. The research result shows that 4 out of 7 indicators are within ‘good category’. The other 3 indicators comprising facilities and infrastructure, human resource, and finance are positionedwithin ‘insufficient category’ for promoting capacity building programe.Therefore, there are two suggestions Lahat District Administrative Police (Pamong Praja Police) Unit Office may take into action to develop its organization capacity: first, improving facilities and infrastructures through procurement; second, conducting continuous high-impact training and education.